Evidence for prevalent Z = 6 magic number in neutron-rich carbon isotopes - D. T. Tran (Nature Portfolio, 2018)
Magic numbers are associated with the stability of atomic nuclei. Here, the authors analyse the proton radii, binding energies and electric quadrupole transition rates of neutron-rich carbon isotopes at proton number six and use nuclear structure models to support the magic number Z = 6.